Bulletin 81 The Smelting of Copper Ores in the Electric Furnace - Dorsey A. Lyon; Robert M. Keeney (The National Institute for Occupational Safety and Health (NIOSH), 1915)
This bulletin is one of a series dealing with the application of the electric furnace to the smelting of ores and the manufacture of alloys, and is published by the Bureau of Mines in the endeavor to increase efficiency in metallurgical processes. The bulletin presents, first, a critical discussion of the possibility of smelting copper ores in the electric furnace; second, the results of the experimental work of other investigators on the electric smelting of copper; third, the results of experiments by the authors on the electric smelting of native copper concentrates and sulphide copper ores; and, fourth, a comparison of the electric furnace with the blast furnace and reverberatory furnace for copper smelting. Before considering the electric smelting of copper ores the reader should understand that the electric furnace was not developed as a competitor of the combustion furnace, but for the purpose of doing high-temperature work that can not be done in the combustion furnace, and for the treatment of ores from deposits that are in regions where fuel is scarce and costly but hydroelectric power is comparatively cheap, as in Chile, and in certain parts of Canada, the United States, and Mexico. Furthermore, it is not the object of this report to try to prove that the electric furnace should replace the reverberatory or the blast furnace, as used at present in smelting copper ores, but to show that the electric furnace may be used with advantage in localities where conditions are not favorable to the use of the reverberatory or the blast furnace. For example, otherwise valuable ore deposits may be situated in a district so remote from, or inaccessible by, railway that the cost of get- ting coke for smelting, or of transporting the ore to a smelter, is pro- hibitive. If there is sufficient water power at hand, from which electric power can be developed at a reasonable cost, and this electric power is used for smelting the ore in an electric furnace, with subse- quent bessemerizing, if necessary, the concentrated product may be